2011
DOI: 10.1007/s00595-011-0054-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of thymidylate synthase and dihydropyrimidine dehydrogenase mRNA in intrahepatic cholangiocarcinoma

Abstract: Low DPD mRNA expression was related to macroscopic type and associated with poor prognosis. DPD mRNA expression in tumor cells is suggested to be an important regulator of malignant behavior in IHCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Studies undertaken to determine the molecular mechanisms of intrinsic and acquired resistance to 5-FU have found various alterations of drug target(s) and metabolism (14,15), such as key enzymes of 5-FU anabolism and catabolism including thymidylate synthase (TS) (16), thymidine phosphorylase (TP) (17) and dihydropyrimidine dehydrogenase (DPD). It had been confirmed in tissue and from mRNA levels that negative DPD (not TS) expression is significantly associated with the enhanced tumor cell proliferation and poorer prognosis in patients with intrahepatic cholangiocarcinoma (18,19). In addition, altered expression of apoptosis-regulating genes also can lead to resistance to 5-FU (20).…”
Section: Nk4 Regulates 5-fluorouracil Sensitivity In Cholangiocarcinomentioning
confidence: 97%
“…Studies undertaken to determine the molecular mechanisms of intrinsic and acquired resistance to 5-FU have found various alterations of drug target(s) and metabolism (14,15), such as key enzymes of 5-FU anabolism and catabolism including thymidylate synthase (TS) (16), thymidine phosphorylase (TP) (17) and dihydropyrimidine dehydrogenase (DPD). It had been confirmed in tissue and from mRNA levels that negative DPD (not TS) expression is significantly associated with the enhanced tumor cell proliferation and poorer prognosis in patients with intrahepatic cholangiocarcinoma (18,19). In addition, altered expression of apoptosis-regulating genes also can lead to resistance to 5-FU (20).…”
Section: Nk4 Regulates 5-fluorouracil Sensitivity In Cholangiocarcinomentioning
confidence: 97%
“…8). This map Morine et al (2012) Pre-mRNA splicing The genes found in the literature are characterized by pathway involvement or function depicts SNPs found in five genes known to affect homocysteine levels. Visualizing information in this manner can aid in disease-risk assessment based on constellations of SNPs and environmental and lifestyle factors that individually, or in ensemble, affect probability of developing a disease or risk factor.…”
Section: Utilizes Gene Products Frommentioning
confidence: 99%
“…The authors of a drug-response assay carried out using tumor tissue obtained from intrahepatic CCA concluded that TS mRNA levels could not predict the success of 5-FU chemotherapy [59]. This concept was further supported by in vivo studies, in which the determination of TS mRNA in tumors resected surgically from patients with intrahepatic CCA revealed no correlation between expression and prognosis [77]. In contrast, a phase II trial in patients with incurable biliary cancer treated with gemcitabine plus capecitabine reported that the longest overall survival was found in patients with the TS 5′GC polymorphism, i.e., double (2R) or triple (3R) 28-bp tandem repeats plus G>C substitution at the 12 th nucleotide in the second repeat of the 3R allele (3RG>3RC) [78]; this results in decreased RNA stability and hence a lower transcriptional activity of TS.…”
Section: Mechanisms Of Chemoresistance Type 3 Targetsmentioning
confidence: 99%